A history of Kilkenny College, 1538-1903 : a study of the vicissitudes of a privately endowed grammar school in Ireland - Welch, Howard Terence (Trinity College (Dublin, Ireland). School of Education, 2002)
A History of Kilkenny College, 1538 -1903: A study of the vicissitudes of a privately endowed grammar school in Ireland. This thesis examines the history of Kilkenny College, Ireland's oldest grammar school, from its foundation in 1538 until the management of the College was taken over by the Incorporated Society for the Promotion of Protestant Schools in Ireland in 1903. The philosopher George Berkeley, the writer Jonathan Swift and the dramatist William Congreve are some of the College's notable former pupils. Chapter One examines the establishment of the College by the earl and countess of Ormond until its closure in 1566. In doing so the Ormonds were continuing in a tradition of education which had existed in Kilkermy since monastic times and the twelfth century foundation of the college of the vicars choral, connected to St. Canice's Cathedral. Chapter Two argues that through the orthodox teachings of Peter White, Master of the College from 1557 until 1566, several former students of the College had a considerable impact on the Counter-Reformation within both Ireland and the continent. The re-establishment of the College c.1666 by James Butler, the first duke of Ormond, and the granting of an endowment of one hundred and forty pounds to the College along with a Charter and Statutes in 1685, form the subject of Chapter Three. This Charter and Statutes were closely linked to the Statutes which were granted to Witney Grammar School, Oxfordshire in 1674, the connection being the Rev. Dr. Hinton, who was Master of both Witney and the College, a link which is analysed in Chapter Four. In 1688 the College was closed and replaced by a Roman Catholic institution which developed into the short-lived Royal College of St. Canice, chartered as a university by James I in 1690 but reopened after the Williamite victory at the Boyne.
Keywords: Education, Ph.D.; Ph.D. Trinity College Dublin